Living on the lake in prehistoric Europe : 150 years of lake-dwelling research - Menotti, Francesco (Routledge, 2004)
A survey of the history and current state of research on lake-dwelling in Europe. Timed to mark the 150th anniversary of the beginning of the study of prehistoric lake-dwellers.